2003
DOI: 10.1002/mds.10497
|View full text |Cite
|
Sign up to set email alerts
|

Emotion recognition in patients with idiopathic Parkinson's disease

Abstract: Emotion recognition (ER) was examined in 64 patients with idiopathic Parkinson's disease (PD; 56 bilateral and 8 right-sided) and 64 matched healthy volunteers. Participants were administered an ER battery, consisting of the following subscores: overall ER (OER), overall facial ER, facial emotion identification (FEI) and discrimination, overall prosodic ER, and prosodic emotion identification (PEI) and discrimination. Measures of visuospatial functions, auditory attention, and depression were also administered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
76
4
7

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(93 citation statements)
references
References 71 publications
(150 reference statements)
6
76
4
7
Order By: Relevance
“…They reported a deficit in patients whatever the treatment condition, but found a greater one among unmedicated patients. This is consistent with the positive correlation between patients' performance and daily levodopa‐equivalent dose (LED) found by Assogna et al45 However, no other authors who looked for such correlations found this result 19, 28, 38, 45, 64, 65, 67, 75. Otherwise, several studies have reported a beneficial effect of DRT on FER in PD.…”
Section: Discrepancies In Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…They reported a deficit in patients whatever the treatment condition, but found a greater one among unmedicated patients. This is consistent with the positive correlation between patients' performance and daily levodopa‐equivalent dose (LED) found by Assogna et al45 However, no other authors who looked for such correlations found this result 19, 28, 38, 45, 64, 65, 67, 75. Otherwise, several studies have reported a beneficial effect of DRT on FER in PD.…”
Section: Discrepancies In Resultssupporting
confidence: 84%
“…Indeed, about 30% of the reviewed studies did not examine its effect on the recognition of specific emotions but calculated an overall score encompassing all the displayed emotions 4, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29. Moreover, authors did not manipulate the same set of stimuli, and some only used a small subset 23, 30, 31, 32, 33, 34, 35.…”
Section: Facial Emotion Recognition In Pdmentioning
confidence: 99%
“…Another important deficit that some individuals with PD frequently demonstrate is the inability to react appropriately to the facial expressions of others or to produce a diversity of facial expressions (Ariatti, Benuzzi, & Nichelli, 2008;Scott, Caird, & Williams, 1984;Yip, Lee, Ho, Tsang, & Li, 2003). Moreover, it is also challenging for some people with PD to accurately produce or perceive the prosodic aspects of speech, specifically angry or questioning statements (Scott et al, 1984).…”
Section: Sensory or Perceptual Deficits In Parkinson's Diseasementioning
confidence: 99%
“…A commonly drawn inference is that the emotion recognition deficit experienced by individuals with PD is likely to be cross-modal (Peron et al, 2010), yet only a small number of studies have examined emotion recognition performance in both facial and prosodic modalities with same Emotional state classification in PD 4 participants. A number of these report found deficits in both modalities (Ariatti et al, 2008;Yip et al, 2003), whereas others found problems in only one modality (facial, Pell and Leonard, 2003); prosody, Pell and Leonard, 2005), and at least one failed to find deficits in recognition in either modality (Caekebeke et al, 1991).…”
Section: Introductionmentioning
confidence: 96%
“…Evidence indicates the individuals with PD have deficits in recognizing emotions from prosody (Dara et al, 2008;Pell and Leonard, 2003;Yip et al, 2003) and facial expressions (Ariatti et al, 2008;Clark et al, 2008;Dujardin et al, 2004), although not all findings have been consistent. Several studies have failed to find impaired performance in the recognition of facial expressions related to emotion in their PD samples (Adolphs et al, 1998;Pell and Leonard, 2005), whereas others have failed to find deficits in recognition from prosody (Clark et al, 2008;Kan et al, 2002).…”
Section: Introductionmentioning
confidence: 99%